2015
DOI: 10.1001/jamafacial.2015.0171
|View full text |Cite
|
Sign up to set email alerts
|

Use of Laser-Assisted Indocyanine Green Angiography for Early Division of the Forehead Flap Pedicle

Abstract: The paramedian forehead flap is used to reconstruct medium to large nasal defects. The staged nature, with its vascular pedicle bridging the medial eyebrow to the nose, results in significant facial deformity. Earlier division lessens this morbidity. OBJECTIVES To quantify flap neovascularization 2 weeks after the initial flap transfer and to describe an algorithm for earlier division of the flap pedicle in select patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 38 publications
0
58
0
Order By: Relevance
“…Forty-nine articles, including 1996 surgical flaps, were selected for the review. Study designs included prospective cohort studies (n = 27), 31,34,35,38,39,[41][42][43][47][48][49][50]56,[58][59][60][62][63][64][65][66][67][68][69][70][71] retrospective cohort studies (n = 16), [25][26][27]29,32,33,36,40,44,45,51,55,57,61,72 prospective pilot studies (n = 3), 28,37,52 and retrospective case series (n = 3). 46,53,54 No randomized controlled trials have been performed yet that concern ICGA in plastic and reconstructive flap surgery.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Forty-nine articles, including 1996 surgical flaps, were selected for the review. Study designs included prospective cohort studies (n = 27), 31,34,35,38,39,[41][42][43][47][48][49][50]56,[58][59][60][62][63][64][65][66][67][68][69][70][71] retrospective cohort studies (n = 16), [25][26][27]29,32,33,36,40,44,45,51,55,57,61,72 prospective pilot studies (n = 3), 28,37,52 and retrospective case series (n = 3). 46,53,54 No randomized controlled trials have been performed yet that concern ICGA in plastic and reconstructive flap surgery.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Suroamo achieved promising results with his 1 week accelerated takedown, but cautioned against its use poorly controlled diabetes or heavy tobacco users. Surowitz and Most, 6 who studied division of the pedicle at 2 weeks, agreed with the careful selection of appropriate patients based on comorbidities and smoking status when determining how long to delay the second stage. Several authors have even described single-stage nasal reconstruction using the forehead flap but have noted increased rates of complications that have the potential to ultimately compromise the reconstruction.…”
Section: Discussionmentioning
confidence: 97%
“…1,5 Of these, the inability to wear eyeglasses has perhaps the most direct effect on the patient’s ability to perform activities of daily living and is underappreciated in the elderly population in particular, many of whom do not wear contact lenses. 6 The inability to wear their glasses results in impaired ability to read, drive, or perform other basic activities during the 2 to 3 weeks between surgeries. 3 For some patients, this prohibits the use of the paramedian forehead flap for nasal reconstruction in otherwise surgically appropriate candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Flap viability correlates directly to flap vascularization. In a prospective study, Surowitz and Most investigated the progression of relative perfusion of forehead flaps throughout the healing process. Using intraoperative laser fluorescence angiography, the authors reported that significant neovascularization occurs by the end of week 1.…”
Section: Literature Reviewmentioning
confidence: 99%